Strategi Pembinaan Warga Gereja - Megawati Manullang; Winda Kurniati Situmorang; Chronika Naftali Pasaribu; Valen Aridison Tamba (Jurnal Pengabdian Kepada Masyarakat, 2024)
The strategy of fostering church members is an effort aimed at building faith, congregational character, and congregational involvement in spiritual life and service. The main goal of the church member development strategy is to create a community environment that is deeply rooted in Christian values, able to face challenges today, and relevant in social contribution. In this strategy, of course, the church has an important role in carrying out faith development through PA, prayer and empowerment in service and social in this development, a step is needed so that this development can run well and is expected to be able to form a congregation that supports each other, becomes a witness of Christ in the midst of society and is able to collaborate with each other to realize a life that has an impact on others. For that, the purpose of writing this article is to inform how the right strategy is in development and to fulfill group assignments in the church member development course with qualitative methods through ebooks, articles and sharing sources obtained and implying them in everyday life.